Bleach. 43, Kingdom of hollows - Kubo, Tite (Kubo, Tite. Bleach (VIZ Media), 2012)
"The battle against Aizen's Espadas continues as the Soul Reapers search for a way to defeat Barragan's terrifying abilities. Meanwhile, Shunsui will need every trick in his bag to compete against Stark."